‘It was no way to live, really’: uncovering the embodied harms of image-based sexual abuse on female victim-survivors in Singapore - Lim, Jia Ying (Nanyang Technological University, 2022)
From illicit sex-themed chatgroups to voyeurism incidents, Singapore is experiencing an emerging pattern of image-based sexual abuse (IBSA) against women and girls. Despite its growing prevalence, the effects, or harms, of IBSA remain understudied in extant literature. To fill the research gap, the paper aims to answer the following question: What are the harms of IBSA experienced by female victim-survivors in Singapore? A qualitative thematic analysis on the experiences of 24 victim-survivors is conducted to illuminate five overarching types of harms of IBSA: (1) shame and self-condemnation; (2) loss of control over self-presentation; (3) siege mentality; (4) permanent scarring; and (5) ontological destruction. I further map out how and why virtual objects (such as intimate images) and actions (such as their non-consensual circulation) come to hurt victim-survivors' corporeal bodies in specific ways. In doing so, I advance the claim that these harms are embodied and inflicted upon the socially and digitally mediated bodies of victim-survivors. Lastly, policy recommendations to prevent the perpetuation of IBSA are furnished.